Seguimiento anual de la parasitosis gastrointestinal de venados cola blanca Odocoileus virginianus (Artiodactyla: Cervidae) en cautiverio en Yucatán, México - Montes Pérez, Rúben C (1998)
Gastrointestinal parasites, and egg and oocyst output in the faeces of captive white-tailed deer (Odocoileus virginianus yucatanensis) were recorded in Yucatan, Mexico. Feces were obtained from from January through Deeember 1995 (ten samples every two weeks per place). Samples were proeessed by flotation and the McMaster techniques. Faecal cultures for L3 larvae were made by the Corticelli-Lai technique. Oocysts in faeces \vere cultured in 2% potasium dicromate. Seven genera were determined (Haemonchus spp., Cooperia spp, Isospora spp., Eimeria spp., Trichuris spp., Strongyloides spp. and Moniezia spp.) which represent five orders. The most frequent genera were Haemonchus, Isospora and Eimeria. The genus Isospora is reported for the first time in deer of this region, although it was not possible to explain the source of this parasite. The frequency and level of faecal egg and oocyst outputs were variable during the year and increased during the rainy season. There was a positive correlation between relative humidity, environmental temperature and rainfall with lhe coccidia and strongylida orders. In the central zone of Yucatan the meteorological conditions during the rainy season are favourable for the development of gastrointestinal parasitism whieh enable an inereased risk of infeelion for deer.